Gender differences in health information behaviour: a Finnish population-based survey - Ek, Stefan (Health promotion international, 2015)
Narrowing the gaps in health outcomes, including those between men and women, has been a pronounced goal on the agenda of the Finnish health authorities since the mid-1980s. But still there is a huge gap in favour of women when it comes to life expectancy at birth. People's health information behaviour, that is how people seek, obtain, evaluate, categorize and use relevant health-related information to perform desired health behaviours, is a critical prerequisite to appropriate and consistent performances of these behaviours. With respect to gender, it has been noted that men often are unwilling and lack the motivation to engage with health-related information. The purpose of this study was to investigate how gender affects health information behaviour in the Finnish population aged 18-65 years. The survey data were collected via a questionnaire which was posted to a representative cross section consisting of 1500 Finnish citizens. The statistical analysis consists of ANOVA F-tests and Fisher's exact tests. The results show that women were more interested in and reported much more active seeking of health-related information, paid more attention to potential worldwide pandemics and were much more attentive as to how the goods they purchase in everyday life affect their health than men did. Women also reported receiving far more informal health-related information from close family members, other kin and friends/workmates than men did. Thus, to succeed in public health promotion and interventions the measures taken should be much more sensitive to the gender gap in health information behaviour.